Assessing the effectiveness of perioperative s-ketamine on new-onset headache after resective epilepsy surgery (ESPAIN-trial): protocol for a randomised, double-blind, placebo-controlled trial. Issue 8 (3rd September 2019) - Sloekers, Jiske Cornelia Theresa; Bos, Michael; Hoogland, Govert; Bastiaenen, Caroline; van Kuijk, Sander; Theunissen, Maurice; Rijkers, Kim; Dings, Jim; Colon, Albert; Rouhl, Rob P W; Schijns, Olaf Elisabeth Maria Ghislaine
Abstract : Introduction: Effective treatment of new-onset headache after craniotomy, especially anterior temporal lobectomy (ATL) and amygdalohippocampectomy for drug-resistant temporal lobe epilepsy, is a challenge. The current practice, acetaminophen combined with opioids is often reported by patients as insufficient and sometimes accompanied by opioid-related adverse effects. Based on expert opinion, anaesthesiologists therefore frequently consider s-ketamine as add-on therapy. This randomised parallel group design trial compares s-ketamine with a placebo as add on medication to a multimodal pain approach. Methods and analysis: In total 62 adult participants, undergoing ATL for drug resistant epilepsy under general anaesthesia, will be randomised to either receive a 0.25 mg/kg bolus followed by a continuous infusion of 0.1 mg/kg/hour of s-ketamine or placebo (0.9% NaCl) starting before incision and continued for 48 hours as an addition to acetaminophen and opioids administered in a patient-controlled analgesia pump. The primary outcome measure is the cumulative postoperative opioid consumption. Patient recruitment started August 2018 and will end in 2021. Secondary outcome measures are postoperative pain intensity scores, psychological parameters, length of hospital stay and adverse events and will be reassessed at 3 and 6 months after surgery, with a baseline measurement preoperatively. All data are collected by researchers who are blinded to the treatment. The data will be analysed by multivariable linear mixed-effects regression. Ethics and dissemination: Ethical approval has been given by the local medical ethical committee (NL61666.068.17). This study will be conducted in accordance with the Dutch Medical Research Involving Human Subjects Act and the Declaration of Helsinki. The results of this trial will be publicly disclosed and submitted for publication in an international peer-reviewed scientific journal. Trial registration number: NTR6480.